EFEKTIVITAS MANAJEMEN PERPUSTAKAAN - Rifatunisa, Adinda; Rahmawati, Ima; Kusyanti, Ella (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
This research aims to evaluate how management is implemented at the Library of SMAN 1 Cibungbulang. The research method employed is qualitative descriptive, with data collection conducted through interviews and documentation. Data analysis is carried out descriptively, wherein the research findings are presented in written form to explain the obtained results and then systematically analyzed. The results indicate that library management at SMAN 1 Cibungbulang is well-managed. Planning is well-structured and integrated into both short-term and long-term work programs. The library continues to receive support from the school principal and maintains an annual book as a form of managerial accountability. Furthermore, the organizational structure and division of tasks in library services are well-arranged. However, there are areas that need attention, namely the absence of specialized library staff responsible for information technology services.